The role of ethnic, family, and social capital in intergenerational social mobility among the Argentines and Moroccans in Galicia, Spain - Laiz Moreira, Sofia (Dve domovini, 2025)
The paper’s main objective is to present the results of research aimed at analyzing the intergenerational social mobility processes linked to migration in Argentine and Moroccan families settled in Galicia, Spain. By examining family strategies, the study analyzes the varying mobilization of social, financial, and human capital, intersecting with ethnic capital. The results point out the complex interaction and interrelationship of different conditioning elements (macro, meso, and micro-social determinants) and make it plain that there is a real capacity for agency of particular descendants within given structures, despite the barriers imposed by public policies, labor market discrimination dynamics, and the socioeconomic situation in Spain.
Keywords: Argentinci; Argentines; capital; druge generacije; družbena mobilnost; ethnicity; etnična pripadnost; kapital; Maročani; migracije; migration; Moroccans; second generations; social mobility; Spain